The Influence Of Audio-Visual Media On Knowledge About Menarche Among Female Students With Disabilities In Bengkulu City In 202 - Nina Merita; Mepi Sulastri; Nimas Ayu Lestari (Utan Kayu Publishing, 2025)
Menarche is the first sign of puberty in adolescent girls, marking the maturity of reproductive function. Lack of knowledge about menarche can cause anxiety, especially among students with disabilities. Audio-visual media are considered effective because they can convey information in a more interesting and easily understood way for children with special needs (Pratiwi et al., 2022). The purpose of this study was to determine the effect of audio-visual media on knowledge about menarche among female students with disabilities in Bengkulu City in 2025. The research method used was a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 30 female students with disabilities who had not yet experienced menarche, selected using probability sampling techniques. Data collection was conducted using a questionnaire that had been tested for validity and reliability. Data analysis was performed using the Wilcoxon test. The results showed that before being exposed to audio-visual media, the majority of respondents were in the low knowledge category, with 19 individuals (63.3%), 9 individuals (30%) in the adequate category, and 2 individuals (6.7%) in the good category. After being provided with audio-visual media, almost all respondents were in the good category, namely 28 (93.3%) and 2 (6.7%) in the adequate category. The Wilcoxon test results showed a p-value of 0.001 (p 0.05), indicating a significant effect of audio-visual media on improving knowledge about menarche among disabled female students. Conclusion: Audio-visual media significantly influences the improvement of knowledge about menarche among disabled female students. This medium can serve as an effective educational alternative in reproductive health education.